Mathematical modelling and experimentation of soy wax PCM solar tank using response surface method - Ghabour, Rajab; Korzenszky, Péter (Analecta Technica Szegedinensia, 2020)
Worldwide, governments tend to reduce the CO2 emissions, and the storage of the solar energy system is still considered the most challenging problem to solve under the current state. Mainly, in relatively cold countries, as domestic hot water or for heat process services, where the loss in the tank is huge. Any improvement in the design can achieve a higher solar yield. Since water is the usual medium for heat storage, the integration with phase change material (PCM) can store energy when there is abundant energy and release it when it is needed. In this study, we conducted a capsulated PCM soy wax 52⁰C in an insulated water tank filled with 5 litres of water. To estimate the appropriate number of samples and the quantity of the PCM at two temperature levels using the response surface method with non-linear correlation for the charging phase. The results show 3.16, 0.95, 0.38 first degree magnitude effect for temperature, sample numbers, and wax quantity respectively and 0.29, -0.38 second-degree magnitude effect for quantity and temperature. In addition, an illustration of each two-factors interaction contour plots.